2019
DOI: 10.1186/s13054-019-2436-3
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative pupillometry for the monitoring of intracranial hypertension in patients with severe traumatic brain injury

Abstract: Background: Elevated intracranial pressure (ICP) is frequent after traumatic brain injury (TBI) and may cause abnormal pupillary reactivity, which in turn is associated with a worse prognosis. Using automated infrared pupillometry, we examined the relationship between the Neurological Pupil index (NPi) and invasive ICP in patients with severe TBI. Methods: This was an observational cohort of consecutive subjects with severe TBI (Glasgow Coma Scale [GCS] < 9 with abnormal lesions on head CT) who underwent paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 120 publications
(103 citation statements)
references
References 31 publications
3
85
0
3
Order By: Relevance
“…1. In the subset of patients in whom pupillometry measurements were performed at days 6 and 7 (n = 30), q-PLR remained significantly lower in patients with delirium (median 22 [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] vs. 30 [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] in non-delirious patients at day 6, and 27 [25][26][27][28][29][30][31] vs. 35 [27][28][29][30][31][32][33][34][35][36][37][38] at day 7; both p < 0.05).…”
Section: Associations Between Icu Delirium and Quantitative Pupillarymentioning
confidence: 99%
See 1 more Smart Citation
“…1. In the subset of patients in whom pupillometry measurements were performed at days 6 and 7 (n = 30), q-PLR remained significantly lower in patients with delirium (median 22 [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] vs. 30 [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] in non-delirious patients at day 6, and 27 [25][26][27][28][29][30][31] vs. 35 [27][28][29][30][31][32][33][34][35][36][37][38] at day 7; both p < 0.05).…”
Section: Associations Between Icu Delirium and Quantitative Pupillarymentioning
confidence: 99%
“…Neuroimaging was not systematically performed, but we excluded all patients admitted for a primary acute brain injury or with a previous known neurological disease thereby limiting as much as possible intrinsic brain factors that may potentially alter pupillometry assessment [42,43]. Furthermore, pupillometry measurements were performed by an experienced research ICU physician or nurse, thereby guaranteeing data reliability and quality, and the pupillometry data were blinded to clinicians involved in patient care.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Jahns et al assessed 54 patients with severe TBI with abnormal lesions on head computed tomography (CT) imaging who underwent parenchymal ICP monitoring and repeated NPi assessment through four consecutive measurements over intervals of 6 h prior to sustained elevated ICP >20 mmHg and found that episodes of elevated ICP correlated with a concomitant decrease in NPi. Sustained abnormal NPi was in turn associated with a more complicated ICP course and worse outcome [14].…”
Section: Traumatic Brain Injurymentioning
confidence: 99%
“…Additionally, the rate of abnormal NPi was higher in patients who went on to have a poor outcome versus good outcome (15% vs 0%, P ¼ .002) as defined by Glasgow Outcome Scale after 6 months. 58 In addition to detecting increased ICP, changes in pupillometry have been shown to precede TTH. A small study of 3 patients with a total of 12 independent TTH events evaluated with pupillometry found that the NPi was zero in 58% of cases of TTH and abnormal in the remaining cases.…”
Section: Increased Icp and Herniationmentioning
confidence: 99%